2017
DOI: 10.1158/0008-5472.can-17-0907
|View full text |Cite
|
Sign up to set email alerts
|

ATG5 Mediates a Positive Feedback Loop between Wnt Signaling and Autophagy in Melanoma

Abstract: Autophagy mediates resistance to various anticancer agents. In melanoma, resistance to targeted therapy has been linked to expression of Wnt5A, an intrinsic inhibitor of β-catenin, which also promotes invasion. In this study, we assessed the interplay between Wnt5A and autophagy by combining expression studies in human clinical biopsies with functional analyses in cell lines and mouse models. Melanoma cells with high Wnt5A and low β-catenin displayed increased basal autophagy. Genetic blockade of autophagy rev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 51 publications
3
14
0
Order By: Relevance
“…Notably, the release of HSP70 was not found to be due simply to a cell death-dependent mechanism, as dacarbazine chemotherapy readily induced tumor apoptosis in the BRAF V600E melanoma model but did not induce significant levels of HSP70 release. Although HSP70 has been identified within tumor-derived exosomes, prior studies have also suggested that soluble HSP70 may be released 18,38,39). However, a mechanistic description of how Wnt5a promotes immune tolerance and immunotherapy resistance remains incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the release of HSP70 was not found to be due simply to a cell death-dependent mechanism, as dacarbazine chemotherapy readily induced tumor apoptosis in the BRAF V600E melanoma model but did not induce significant levels of HSP70 release. Although HSP70 has been identified within tumor-derived exosomes, prior studies have also suggested that soluble HSP70 may be released 18,38,39). However, a mechanistic description of how Wnt5a promotes immune tolerance and immunotherapy resistance remains incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that WNT5A increases autophagy, which mediates resistance to various anticancer drugs. Knocking down autophagy-related gene 5 (ATG5) in WNT5A high melanoma cells caused a reduction of the WNT5A level and induction of β-catenin [ 130 ].…”
Section: Wnt Signaling In Melanomamentioning
confidence: 99%
“…Certain regulators relevant for melanoma can inhibit autophagy as shown for neural cell adhesion molecule (NCAM) [97], minichromosome maintenance protein 7 (MCM7) [98] and Wingless-type (WNT)/β-catenin cascade [99]. In line with this, high level of WNT5a, which regulates the activity of non-canonical WNT signaling pathway, and low level of β-catenin were associated with increased basal autophagy in melanoma cells [100]. In turn, downregulation of ATG5 in WNT5a high melanoma cells was associated with lower level of WNT5a and increased level of β-catenin [100], supporting the conclusion that autophagy is inversely correlated with the activity of canonical WNT/β-catenin signaling pathway.…”
Section: Autophagy In Melanomamentioning
confidence: 83%